Analysis of Engine Propeller Matching of DC Motor as a Main Propulsion - Eddy Setyo Koenhardono; Juniarko Prananda; Ekaprana Danian (Institut Teknologi Sepuluh Nopember, 2017)
The development of ship always searches through the most benefits system for reducing costs of propulsion system without increase pollution. Diesel propulsion system or also known as conventional propulsion system is efficient but requires high operating costs and increase high level of marine pollution. Electrical propulsion system is using electric motors as the prime mover of the propeller. There are 2 types of electric motors that will be used for research of electric propulsion system, there are; DC motors and three-phases induction motor. As the use of DC motor as a prime mover for this electrical propulsion system, this study determines the characteristic between voltage terminal with torque and also field current with torque. It results that torque produced by the DC motor is in the same magnitude with the speed (RPM). The higher the speed have shaped the value of the torque. The input and terminal voltages adjusts all variables and results. In this study, different field voltage creates different pattern of motor envelope. Its manner to propeller curve occurs total different results. With field voltage of 50 V, the ranges of motor envelope immoveable in the point of 150% of present speed and 160%. While field voltage of 60 V serves larger ranges of motor envelope which possible to reach further than 50 V curve.